2004
DOI: 10.22358/jafs/67618/2004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary fibre fractions from different cereals and microbial enzyme supplementation on performance, ileal viscosity and short-chain fatty acid concentrations in the caeca of broiler chickens

Abstract: A fi ve-week-long experiment was performed on 960 one-day-old Cobb 500 cockerels divided randomly into ten experimental groups of 12 cages (replicates) of 8 birds each. The objective of the experiment was to estimate the effect of non-starch polysaccharides (NSP) derived from various cereals and addition of microbial enzyme preparations on growth performance, ileal viscosity, liver weight and concentration of short-chain fatty acids in broiler chicken caeca. Barley and oats, hulless barley, naked oats, and rye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 13 publications
4
14
2
Order By: Relevance
“…This is consistent with the results obtained by Choct et al (1999) and Józefiak et al (2004). The lower activity of microbial enzymes observed in the present study may indicate that enzymatic preparations decreased the amount of easily fermentable carbohydrates in caecal digesta.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the results obtained by Choct et al (1999) and Józefiak et al (2004). The lower activity of microbial enzymes observed in the present study may indicate that enzymatic preparations decreased the amount of easily fermentable carbohydrates in caecal digesta.…”
Section: Discussionsupporting
confidence: 93%
“…The addition of exogenous enzymes increased the concentration of SCFA, mainly of acetic acid, in caecal digesta. In the experiment of Józefiak et al (2004), the increase in SCFA concentration was more distinct: almost two times higher in broilers fed barley-or oat-diets supplemented with xylanase and protease. In other studies, enzymatic preparations added to rye diets did not increase the SCFA concentration in caecal digesta (Lázaro et al, 2003).…”
mentioning
confidence: 90%
“…Smits et al (2000) implied that if the viscous properties of NSP were eliminated in broiler chicken feed then the nutrient value of some fats would be improved. Jozefiak et al (2004) found that it was likely not total NSP that influenced intestinal viscosity in broiler chickens, but the NSP type. In addition maybe enzyme supplementation, since diets with viscous components and microbial enzymes probably prevented formation of viscous chyme.…”
Section: Energy Dilution Of Feedmentioning
confidence: 97%
“…Soluble fibre in mammals and poultry tend to increase digesta viscosity and retard absorption of nutrients (Krogdahl et al, 2005), while insoluble fibre tend to increase digesta transit, resulting in reduced absorption time. In experiments with broiler chickens some dietary NSP (non starch polysaccharides) increased digestion viscosity and reduced performance (Razdan et al, 1997;Jozefiak et al, 2004). Digestibility of protein and fat has also shown to be reduced with increased NSP content (Smits et al, 2000;Saki and Alipana, 2005).…”
Section: Energy Dilution Of Feedmentioning
confidence: 99%
See 1 more Smart Citation